Calculation of the vacuum pressure gradient in field emission displays - Degasperi, F. T.; Mammana, V; Verardi, SLL; Baranauskas, V (Elsevier B.V., 2001)
The usual design of field-emission displays (FEDs) often results in high vacuum pressure gradients inside the glass plates of the device, and this is the main limitation to the widespread availability of large area FEDs. In this paper, we perform theoretical calculations using the finite element method for determining the pressure distributions in several pumping configurations, including a new FED configuration known as porous FED or pFED. The approach here is capable of clarifying the design issues influencing the final pressure relevant to the field-emission display devices. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: Field-Emission Displays; design; FED; vacuum